PROGRAM ASSESSMENT OF CREDIT POINTS OF TEACHER PROFESSIONAL DEVELOPMENT IN KUTAI TIMUR - Jamalludin Jamalludin; Suryadi Suryadi; Dwi Nugroho Hidayanto (Journal of International Conference Proceedings (JICP), 2019)
The aim of this research was to program the assessment of credit points of teacher professional development in Kutai Timur. This study was used discrepancy evaluation model. In this program research, program research design includes elements are: that evaluation focus, collecting data, analyzing data, and conclusions of evaluation. The result shows that: (1) teachers can not collect 12 points in the credit element of professional development, (2) teachers do not understand the systematics of writing scientific papers to be proposed in the assessment of credit rate scientific papers professional development of teachers, and (3) teachers dishonest in preparing scientific papers in the assessment of credit rate scientific papers professional development Based on the results. It was recommended that the goverment of Kutai Timur was improve the quality of teachers, namely: (1) encourage teachers willing to improve themselves, increase knowledge and skills that can be assessed by the number of credits, (2) fostering teachers in their professional development not only of writings paper only.